ASEAN–China Free Trade: The Impact of ACFTA Policies on the Sustainability of Indonesian SMEs - Samudra, Dio (Scimadly Publishing, 2024)
This study explores the impact of the ASEAN-China Free Trade Area (ACFTA) policy on the sustainability of Small and Medium Enterprises (SMEs) in Indonesia. Utilizing a qualitative approach, the research delves into the experiences, perspectives, and challenges faced by SMEs in the context of increased market competition and trade integration. The findings indicate that ACFTA presents both opportunities and challenges for Indonesian SMEs. On one hand, the policy enhances market access and eliminates tariffs on a majority of goods, providing SMEs with potential export opportunities to China. On the other hand, the influx of cheaper Chinese imports poses significant competitive pressures, as many domestic SMEs struggle with production scale and pricing competitiveness. Furthermore, the study highlights the importance of a balanced trade relationship and substantial foreign investment flows from China, which contribute to regional economic integration. However, it also points out the risks associated with over-dependence on foreign capital. To maximize the benefits of ACFTA, the study recommends implementing supportive policies that enhance SMEs' competitiveness, capacity building, and technological adaptation. Government initiatives, including training, financial assistance, and market protection, are crucial in helping SMEs navigate the challenges posed by increased competition. Ultimately, the research underscores the potential for Indonesian SMEs to leverage economic integration for sustainable growth and contribute to national economic development.